Efektivitas Kompres Hangat Jahe Merah terhadap Penurunan Skala Nyeri Arthritis Gout pada Lanjut Usia - Sihotang, Sifra Dosmaria; Nurfitriani, Nurfitriani; Ramadhani, Dwi Yunita; Pebrianti, Dwi Kartika (Jurnal Akademika Baiturrahim Jambi, 2024)
Gout arthritis is a disease that arises due to an increase in uric acid levels in the blood that exceed the threshold. Putri Ayu Health Center ranks first of the 20 puskesmas with the highest gout cases. The study aimed to determine the effectiveness of warm compre of red ginger on reducing the scale of gouty arthritis pain of senior citizens in the Working Area of the Putri Ayu Health Center Jambi City. Pre-Experiment research method with One Group Pre-Post Test design. Data collection techniques through inteviews and pain scale measurements. The total population is 405 people, with a sample of 15 respondents. The analysis of this study was univariate and bivariate with paired t-tests. The results of  this study obtained a pain scale before a warm compress of red ginger averaged 5.00 and after being given an average of 3.20, with a difference of 1.80. The effect of the effectiveness of warm compresses of red ginger on reducing the scale of gouty arthritis pain in senior citizens in the Working Area of the Putri Ayu Health Center Jambi City with a p-value of 0.001. It is expected that warm compresses of red ginger can be one of non-pharmacological therapies that can be used to reduce the scale of gouty arthritis pain in senior citizens. Keywords: gout, pain scale, red ginger compress, senior citizens